Familial influences on internalizing symptomatology in Latino adolescents: An ecological analysis of parent mental health and acculturation dynamics. (25th November 2014) - Smokowski, Paul R.; Rose, Roderick A.; Evans, Caroline B. R.; Cotter, Katie L.; Bower, Meredith; Bacallao, Martica
Abstract: The aim of this study was to examine if family system dynamics (e.g., parent mental health, marriage quality, conflict, and cohesion) that have often been overlooked when studying Latino families play a more important role in predicting adolescent internalizing symptoms than acculturation processes. Data comes from the Latino Acculturation and Health Project, a longitudinal investigation of acculturation in Latino families in North Carolina and Arizona (Smokowski & Bacallao, 2006, 2010). Researchers conducted in-depth, community-based interviews with 258 Latino adolescents and 258 of their parents in metropolitan, small-town, and rural areas. Interviews were conducted at four time points at intervals of approximately 6 months. Parent and adolescent ratings of the adolescent's internalizing symptoms were used as the dependent variable in a longitudinal hierarchical linear model with a rater effects structure. Results showed that parent–adolescent conflict and parent mental health (fear/avoidance of social situations and humiliation sensitivity) were significant predictors of adolescent internalizing symptoms. Acculturation scales were not significant predictors; however, internalizing symptoms decreased with time spent in the United States. Females and adolescents from lower socioeconomic status families reported more internalizing symptoms, while participants who had been in the United States longer reported fewer internalizing symptoms. Implications were discussed.